Fatal Puumala Hantavirus Infection in a Patient with Common Variable Immunodeficiency (CVID) - Steininger, Philipp; Herbst, Larissa; Bihlmaier, Karl; Willam, Carsten; Koerper, Sixten; Schrezenmeier, Hubert; Klueter, Harald; Pfister, Frederick; Amann, Kerstin Ute; Weiss, Sabrina; Krueger, Detlev H.; Zimmermann, Robert; et al. (Microorganisms, 2023)
Puumala hantavirus (PUUV) infections usually show a mild or moderate clinical course, but may sometimes also lead to life-threatening disease. Here, we report on a 60-year-old female patient with common variable immunodeficiency (CVID) who developed a fatal PUUV infection with persistent renal failure, thrombocytopenia, and CNS infection with impaired consciousness and tetraparesis. Hantavirus-specific antibodies could not be detected due to the humoral immunodeficiency. Diagnosis and virological monitoring were based on the quantitative detection of PUUV RNA in blood, cerebrospinal fluid, bronchial lavage, and urine, where viral RNA was found over an unusually extended period of one month. Due to clinical deterioration and virus persistence, treatment with ribavirin was initiated. Additionally, fresh frozen plasma (FFP) from convalescent donors with a history of PUUV infection was administered. Despite viral clearance, the clinical condition of the patient did not improve and the patient died on day 81 of hospitalization. This case underlines the importance of the humoral immune response for the course of PUUV disease and illustrates the need for PCR-based virus diagnostics in those patients. Due to its potential antiviral activity, convalescent plasma should be considered in the therapy of severe hantavirus diseases.
CRIS-Team Scopus Importer:2023-03-10
Keywords: common variable immunodeficiency; convalescent plasma; encephalitis; Puumala hantavirus; ribavirin